English and Pilipino error patterns of second year students in a unit on sentential logic - Galarosa, Lucita Remonde (1977)
The purpose of the study was to compare the error patterns of second year students in a unit on sentential logic. It also aimed to find out if language has significant effects in the logical reasoning ability of the students. The study was conducted on three second-year classes randomly selected from two public high schools in Quezon City. The research instrument used was a 30-item test on sentential logic patterned after that of Eisenberg and McGinty with some different modifications to suit the Philippine setting. The study found out that the reasoning abilities of students in English and in Pilipino sets of verbal premises do not differ significantly. Students commit similar types of errors in logical reasoning in either language. Error patterns were noted only in four of the five types. Those were Law of Detachment, Contrapositive, Invalid Disjunctive Syllogism Inference, and Disjunctive Syllogism types of items.